Direct discourse in the Greek press: from evidentiality to subjectivity - Politis, Periklis; Kakavoulia, Maria (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2006)
Among the ways of discourse representation, direct quotation is the most explicit form of inclusion of a speech event in a discourse. Many researchers have reached the conclusion that Direct Discourse (DD) is the mode par excellence in news reports, and that its function is to ensure faithfulness to an original discourse. This article explores the validity of these claims by comparing the forms and functions of DD in two Greek newspapers, namely I Kathimerini and Ta Nea. Our account relies upon a corpus-based approach to the study of DD forms and a qualitative analysis of a) the speech reporting verbs and b) the functions of DD in the news reports. Statistical information from the corpus provided that the most of the DD forms appeared in very divergent frequencies in the two newspapers. Concerning the functions of DD, we distinguished argumentation, dialogue that sets the scene of a conflict, interview reconstruction, evidence presentation, and legitimization. Moreover, reporting verb selection and source indication brought out the reporter's manipulation of discourse representation. Depth analysis proved that DD's functions are not simply restricted to faithfulness but are further related to the reporter's personal involvement in selecting and processing what to report.